EFEKTIVITAS PIJAT UNTUK MERANGSANG HORMON OKSITOSIN PADA IBU NIFAS PRIMIPARA - Murtiani Murtiani; Novita Ika Wardani; Septalia Isharyanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
Maternal mortality in Indonesia is still quite high, one reason is postpartum hemorrhage. Efforts to prevent postpartum hemorrhage can be done with the administration of oxytocin. The hormone oxytocin plays a role in the process of return of the uterus to its original shape. Oxytocin is also working spur spending reflex ASI Let Down Reflex (LDR).To examine the effectiveness of massage to stimulate the hormone oxytocin in the mother postpartum primiparaThis quasi-experimental research designs, sampling techniques with simple random sampling of 60 people, 30 people in treatment group and 30 controls. The research instrument that is the observation sheet. The massage is done every day, from day 1 to day 14 post partum. TFU measurement observations, kind lochea, weight baby day 1, 4, 7, 10, 14. Statistical test with Mann Whitney.Massage to stimulate the oxytocin hormone has a high effectiveness against changes in the uterine fundus on the day 7 and 10 of 0.023 and 0.0001 (p 0.05), to change the type of lochea on the day 4, 7, 10, 14 amounted to 0.015, 0.001, 0.000, 0.000 (p 0.05), the production of breast milk in the day 7 and 10 of 0.000, 0.031 (p 0.05)